Gabriela Mistral and the incompleteness of her biography - Farías Rojas, Gabriel Arturo (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of this paper is to reflect on Gabriela Mistral’s biography thanks to geographical, historico-philosophical and ethical perspectives. Likewise, analyzing the theories of the chronotope and subjectivity, as well as the biographical space in the construction of one’s own subjectivity, will be of great help to understand the vicissitudes in Gabriela Mistral’s updated biography. The methodology is based on the reconstruction of her memory and her archive against the oblivion of the author’s diversity. As expected results, memory helps us avoid the consolidation of the myth about Mistral in the Republic of Chile.